PEMODELAN DAN SIMULASI JARINGAN TRAFFIC PERKERETA-APIAN MENGGUNAKAN METODE COLOURED PETRI NETS - Sitepu, Surianto
Abstract: In this thesis Coloured Petri Nets method is implemented to control train movement. The traffic between Jakartakota station and Bogor station is analyzed. Using CPN method, train traffic movements are modeled at several big station such as: Jakartakota, Gambir, Manggarai, Pasarminggu, Depokbaru, Depok and Bogor. To verify the model, a software program is made to simulate the traffic based on the model in particular. The result, deadlock condition and trapping can be prevented, safety constraint and overtaking is satisfied. Hence, with CPN model train traffic control is more comprehensible and can be evaluated.